Exhaust emission characteristics study of light and heavy-duty diesel vehicles in India. (January 2022) - Singh, Thokchom Subhaschandra; Rajak, Upendra; Verma, Tikendra Nath; Nashine, Prerana; Mehboob, Hassan; Manokar, A. Muthu; Afzal, Asif
Abstract: A study has been conducted using a portable emission tester (PET) for the city of Imphal, India using twelve (12) key business locations for determining the combustion by-products (exhaust emissions) & their characteristics from both light and heavy-duty diesel vehicles. The ambient temperature varied from 23.5 to 28 °C and humidity to be 65 ± 15% during the course of the study. Higher values of Cx Hy and CO, compared to the standard permissible values, have been observed from light duty diesel (LDD) vehicles, with average values of 430 ppm and 465.4 ppm respectively, while NOx has an average value of 99.2 ppm. Similar characteristics are also witnessed from the heavy-duty diesel (HDD) vehicles with CO and Cx Hy having alarming values of 1585 ppm and 2968 ppm respectively, while NOx have an average value of 140.06 ppm. Using total emission approach, the CO2 emissions have been estimated to be about 38.02*10 5 tons and 1135*10 5 tons from LDD and HDD respectively till 2018. With respect to the present study, HDD have the maximum contribution of Cx Hy, NOx and CO in the atmosphere with values of 76.9%, 69.3% and 58.5% respectively. The authors believed that such alarming emissions from the vehicles would have been controlled if the authorities had performed regular checks and imposed strict laws against heavy emissions from vehicles.